1991
DOI: 10.1007/bf00172378
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum psychosis, infanticide and the law

Abstract: In the past few years postpartum phychosis has been offered as a legal defense in a small number of deeply disturbing infanticide cases in several American jurisdictions. These cases have attracted a great deal of media attention, and fueled public discussion about the mental health of mothers who kill their own babies. From the perspective of the criminologist these cases present an extraordinary pattern of criminal behavior. Not merely a few isolated incidents, but a recurring pattern of the destruction of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Maier‐Katkin (1991) reported that in actual cases of infanticide committed by mothers, half of the verdicts were not‐guilty by reason of insanity. Maier‐Katkin's findings suggest that, in some cases, mothers may not be held fully accountable for crimes against their own children because this behavior, on the part of a mother, is seen as indicative of insanity.…”
Section: Impact Of Parental Role On Verdictmentioning
confidence: 99%
“…Maier‐Katkin (1991) reported that in actual cases of infanticide committed by mothers, half of the verdicts were not‐guilty by reason of insanity. Maier‐Katkin's findings suggest that, in some cases, mothers may not be held fully accountable for crimes against their own children because this behavior, on the part of a mother, is seen as indicative of insanity.…”
Section: Impact Of Parental Role On Verdictmentioning
confidence: 99%
“…Functioning as the realms of norm affirmation and symbolic boundary making (Durkheim, 1960;Erikson, 1966), the criminal courts are not mechanisms for real solutions to social problems such as crimes against children. Those who believe that aggressive identification and prosecution of parental violence against children provides deterrence to these acts, misjudge the issue for several important reasons: first, the deterrence model presumes a ''rational'' actor (Wilson, 2005) while a great majority of parental offenses against children are irrational, highly emotional acts precipitated by extreme stresses of various kinds (ibid; see also Maier-Katkin, 1991;Maier-Katkin & Ogle, 1993;Mann, 1996;Margolin, 1990Margolin, , 1992Ogle, Maier-Katkin, & Bernard, 1996;Wheelwright, 2002). Second, as some researchers on the subject claim (Ashe, 1997;Pelton, 1998), the perceptions of ''draconian'' character and biases in child protection deter even those parents who do not abuse their children from seeking help for them in cases of accidental injuries.…”
Section: Implications and Analysismentioning
confidence: 99%
“…The subject of why the United States did not adopt a comparable statute deserves a separate paper, suffice it to say that through the years there have been forceful and compelling arguments for the adoption of laws separating infanticide from other homicides. Nevertheless, infanticide, including neonaticide and homicide of children older than 1 year, is treated in the Unites States in an ad hoc fashion and an outcome of the case depends on the states' laws and biases of the judges and juries (Maier-Katkin, 1991;Maier-Katkin & Ogle, 1993;Meyer & Oberman, 2001;Oberman, 1996). 3.…”
Section: Notesmentioning
confidence: 99%
“…The statutes are viable only as applied to mothers (not fathers or other relatives) and commonly only during the first twelve months of an infant's life. In the United States, comparable statutes have never been developed, although through the years there have been forceful and well-supported arguments for the adoption of laws separating maternal infanticides from other homicides (Denno 2003;Maier-Katkin 1991;Maier-Katkin and Ogle 1993;Meyer and Oberman 2001;Oberman 1996;Spinelli 2003). Infanticide, including neonaticide and homicide of children older than one year old, is treated in an ad hoc fashion, and outcomes depend on the state's laws as well as on the biases of the judges and juries.…”
Section: Psychiatric Defense: Patriarchy Paternalism or Both?mentioning
confidence: 99%